Academic Library COVID-19 Subject Guides. Issue 3 (1st October 2020) - Fraser-Arnott, Melissa
ABSTRACT: This study reviewed the coronavirus (COVID-19) resources available on the Times Higher Education top 50 research universities websites. Both general coronavirus resource pages and library subject guides dedicated to the pandemic were examined. The results were compiled into a list of 416 links which were then analyzed. The most common content creators (publishers/authors) were (1) government departments and agencies, (2) academic publishers, (3) international and nonprofit organizations, and (4) universities. The most common types of resources included (1) scholarly article collections (publisher databases or preprint collections), (2) consumer health information, (3) data sets including data maps, and (4) media resources. The examination of library subject guides and university COVID-19 resource pages revealed opportunities for collaboration with other university units in the creation of resource lists for different audiences and the creation of information literacy resources with an emphasis on data literacy.